Determinants of Stunting at 6 Weeks in the Northern Cape Province, South Africa - le Roux, Maretha; Nel, Mariette; Walsh, Corinna (Frontiers in Public Health, 2020)
The first 1000 days from conception to 24 months, is a critical period for healthy growth and development. In South Africa, stunting (weight-for-length below -2SD from the WHO reference mean) is a major public health issue with significant health consequences. We determined associations between demographic, health and anthropometric indicators of mothers and their infants. A cross sectional study was conducted in the Northern Cape. All mothers with 5-7 week old babies visiting PHC facilities could participate. A questionnaire was completed in a structured interview with each mother. Age and length of the baby at 6 weeks were used to determine stunting, while weight and height of the mother were measured for body mass index (BMI). Eight hundred questionnaires were completed in 92 facilities. Median age of mothers was 26 years (range 10-46 years) and 44,9% were married. Only 40.1% had completed school or tertiary education and almost 40% relied on a government grant as main source of income. Two-thirds (64,9%) had not planned the pregnancy and 17% were on ART. More than a quarter (26,1%) smoked cigarettes or used snuff during pregnancy, while 9,4% drank alcohol. At six weeks 31% of boys and 14% of girls had a length-for-age below the WHO reference values, while 25,4% of mothers were classified as obese and 24,6% as overweight. More than 70% had a waist circumference above 80cm. Significantly more mothers with stunted babies weighed less [-6kg; -1kg] and were shorter [-4cm; -1cm] than mothers with babies that were not stunted. Compared to babies that were not stunted, significantly more babies of mothers that lived in informal housing [-19.7%; -3.2%], relied on a grant [-19.7%; -3.2%], smoked/ snuffed [7.6%; 23.5%] and used alcohol during pregnancy [0.3%; 11.5%] were stunted. We confirmed the coexistence of under- and over-nutrition among mothers and their babies, possibly indicating that stunting in childhood predisposes to overweight and obesity in adulthood in a vicious cycle that affects generation after generation. Interventions aimed at poverty alleviation and encouraging healthy lifestyles with emphasis on healthy eating, smoking cessation and abstaining from alcohol before pregnancy are urgently required.